Documentación de los procesos misionales de un sistema de gestión de la calidad basado en los requisitos de la norma ISO 9001:2015 en una empresa del sector tecnología (2017)
The company case study belongs to the technology sector and its main activity is to implement a software called Systems, Applications and Products in Data Processing (SAP) that aims to improve processes within organizations and make them more efficient and productive. To carry out the implementation, there are two missionary processes, the first known as Consulting, whose execution is based on project management, and the second is IT Services, which ensures the implementation of the architecture for information and administration of the project. same